2021
DOI: 10.2174/1745017902117010198
|View full text |Cite
|
Sign up to set email alerts
|

Association between Estimated Cardiorespiratory Fitness and Depression among Middle-income Country Adults: Evidence from National Health Survey

Abstract: Objective: This study assessed the relationship between cardiorespiratory fitness (CRF) and depression in adults. Methods: A total of 52,611 individuals aged between 18-59 years old were evaluated for symptoms of depression and CRF. The presence of depressive symptoms was self-report through the Patient Health Questionnaire (PHQ-9), and the CRF was predicted from a non-exercise equation. The association between CRF an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In fact, it is well known that, especially in the elderly, the two parameters can influence each other [71], and that in this age range, physical exercise can stimulate the growth of the social support network [72].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is well known that, especially in the elderly, the two parameters can influence each other [71], and that in this age range, physical exercise can stimulate the growth of the social support network [72].…”
Section: Discussionmentioning
confidence: 99%
“…Third, we had no control over the diets of the study groups; therefore, we do not know the content and the availability of the macronutrients that may have influenced Trp catabolism. Fourth, the degree of stress, depression and anxiety was not evaluated in this population; however, we are considering these evaluations together with CRF—which has been related to improve memory performance and as-sociated with lower depressive symptoms [ 71 , 72 ] in future work involving naval personnel, given the potential of neurological functions of Trp metabolites and exercise for mental health. Finally, the lipid peroxidation was estimated in serum samples by TBA-RS, which measures the MDA concentration; however, other compounds could cause overestimation of MDA concentration, for which in futures studies the lipoperoxidation will be confirmed by chromatographic separation of MDA–TBA adduct [ 40 ].…”
Section: Discussionmentioning
confidence: 99%